Factors contributing to favorable outcome in adults with Bell’s palsy: experience from a tertiary care hospital of Bangladesh - Alam, Dilruba; Habib, Rumana; Islam, Md Rashedul; Rouf, Rushda Sharmin Binte; Habib, Samira Humaira (BIRDEM Medical Journal, 2022)
Background: Bell’s palsy (BP) is the most common cause of lower motor neuron type facial nerve palsy and is one of the most frequently encountered presentations in Neurology. Treatment with corticosteroid and antiviral drugs within 72 hours of onset of symptoms along with supportive treatment is encouraged for better outcome. Despite good prognosis, a significant portion of the patients with BP suffer from disfiguring facial appearance and other complications which remain as great concern of the patients. We aimed to evaluate the factors contributing to favorable outcome in adult with BP. Methods: Data of patients with BP [House-Brackmann (H-B) Grading III and above], who attended and were followed up at the Department of Neurology of BIRDEM General Hospital, Dhaka, Bangladesh between January 2017 and December 2020, were reviewed from hospital records and patients’ personal files. Total 56 adult patients with BP were recruited from hospital records according to eligibility criteria. During recruitment and data analysis, patients of H-B Grade III- IV were considered as lower grade and Grade V-VI were considered as higher grade. During follow up Grade I and II were considered as recovered. Comorbidities including diabetes and hypertension were addressed. Patients with BP who attended within 72 hours of onset of symptoms were prescribed steroid and antiviral drugs, whereas patients attending after 72 hours of onset of symptoms received supportive treatment only. All patients of both the groups received physical therapy for facial asymmetry and medication for eye care along with close monitoring and management of diabetes and other comorbidities. H-B Grades were assessed at onset, after 10 days, at the end of 1st and at 3rd month after facial paralysis and depending upon this Grading patients were finally divided into two groups of favorable (H-B Grade I & II) and unfavorable (H-B Grade III or more) outcome. Univariate and multivariable logistic regression analyses were performed to assess the factors for favorable prognosis. Results: Among the total 56 patients, 45(80.4%) patients had favorable and 11 (19.6%) had unfavorable outcomes at the end of 3rd month. Multivariable logistic regression analysis revealed that younger (at or below 40 year) age group (OR= 1.33; 95% CI, 0.412-4.310, p=0.005), lower H-B Grade at presentation (Grade III – IV) (OR= 2.712; 95% CI, 1.951-3.612, p=0.044) and absence of hypertension (OR=1.14; 95% CI, 0.963- 2.035, p=0.023) were significant. Conclusion: We concluded that younger age group of patients with lower H-B grade at initial presentation and absence of hypertension all are contributing factors for favorable outcomes in adults with Bell’s palsy. BIRDEM Med J 2022; 12(3): 217-222